PENGARUH JUMLAH ANGGOTA DAN MODAL SENDIRI TERHADAP SISA HASIL USAHA KOPERASI UNIT DESA DI KOTA PADANG - Syafni Anita Putri; Yulhendri Yulhendri (Jurnal Ecogen, 2019)
Remaining business results is one of the important things in improving the welfare of members of cooperatives, because cooperatives are one of the forces that drive economic growth. This research is an associative descriptive study using panel data regression analysis method using Eviews version 8. Data was collected by documentation technique, the data in this study are secondary data, namely all Village Unit Cooperatives in Padang City totaling 6 KUD. The dependent variable in this study is the residual business results, while the independent variable is the number of members and own capital. The results of this study stated that the F test obtained a calculated f value of 24,90077 while the f table value of 3.28 so that the calculated f value is greater than the value of the f table and sig probability value. 0,000 <α = 0.05 which means Ho was rejected and Ha was accepted. This shows that there is a joint effect between the number of members (X1) and own capital (X2) on the Remaining Operations (Y) of the Village Unit Cooperative in Padang City. R Square value in this study amounted to 0.577 or 57.7%. This means that the amount of contribution between the number of members and own capital to the rest of the business results is 57.7% while 42.3% is influenced by other factors not examined in this study. Keyword: the number of member, equity, and SHU